2003
DOI: 10.1016/s0304-3959(03)00173-8
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin and gabapentin reduce release of substance P and CGRP from rat spinal tissues only after inflammation or activation of protein kinase C

Abstract: Gabapentin and pregabalin are amino acid derivatives of gamma-amino butyric acid that have anticonvulsant, analgesic, and anxiolytic-like properties in animal models. The mechanisms of these effects, however, are not well understood. To ascertain whether these drugs have effects on sensory neurons, we studied their actions on capsaicin-evoked release of the sensory neuropeptides, substance P and calcitonin gene-related peptide from rat spinal cord slices in vitro. Although release of immunoreactive peptides fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
171
1
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(185 citation statements)
references
References 54 publications
8
171
1
5
Order By: Relevance
“…28 Peripherally-released substance P and CGRP were noted to mediate mechanical hyperalgesia in a peripheral neuropathic pain model. 29 Therefore, pregabalin administered peripherally may affect the release of these mediators and alleviate the hyperalgesia in this type of pain model.…”
Section: Discussionmentioning
confidence: 99%
“…28 Peripherally-released substance P and CGRP were noted to mediate mechanical hyperalgesia in a peripheral neuropathic pain model. 29 Therefore, pregabalin administered peripherally may affect the release of these mediators and alleviate the hyperalgesia in this type of pain model.…”
Section: Discussionmentioning
confidence: 99%
“…Its chemical structure is similar to GABA, but it does not act like GABA, and in particular, does not bind to GABA receptor. Moreover, GP is known to potently bind to the a2-d subunit of voltage-controlled calcium channels, and its binding at this site reduces Ca 2+ influx at presynaptic nerve endings and therefore, reduces the release of several neurotransmitters, which included glutamate and noradrenalin [3,9,11,21]. Given this theoretical background, we wondered whether GP might act as a neuroprotector after SCI, and thus we examined the possibility that GP acts as has a neuroprotective agents.…”
Section: Discussionmentioning
confidence: 99%
“…Gabapentin has proved an anti-inflammatory effect in animal model (19,20). In human, Werner's study showed gabapentin reduces primary mechanical allodynia in acute inflammation following a thermal injury (21).…”
Section: Panah Khahi M Et Almentioning
confidence: 99%